Dietary soy and isoflavone intake and mortality in Korean adults: a prospective cohort study - Sihan Song; Sihan Song; Shinyoung Jun; Hyojee Joung; Jung Eun Lee; Jung Eun Lee (Frontiers in Nutrition)
BackgroundThe association between dietary soy and isoflavone intake and mortality remains inconclusive. This study aimed to examine the relationships of dietary intakes of isoflavones, soy protein, and soy foods with all-cause, cancer, and cardiovascular disease (CVD) mortality in Korean adults.MethodsThis prospective cohort study included 118,450 Korean adults aged 40–79 years from the Health Examinees Study (2004–2013). Dietary intakes of isoflavones, soy protein, and soy foods were assessed using a food frequency questionnaire. Cox proportional hazards models were used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality risk according to quartiles of dietary soy and isoflavone intake.ResultsDuring a median follow-up of 10.1 years (interquartile range: 8.7–11.4 years), 2,614 deaths were documented, including 1,290 from cancer and 389 from CVD. Multivariable analyses showed no significant associations between dietary isoflavone intake and the risk of all-cause and cause-specific mortality. The HRs (95% CIs) comparing the highest vs. the lowest quartile of isoflavone intake were 1.04 (0.93–1.15) for all-cause mortality, 0.98 (0.84–1.14) for cancer mortality, and 1.04 (0.79–1.38) for CVD mortality. Similarly, no significant associations were observed for soy protein or soy food intake in relation to all-cause, cancer, and CVD mortality.ConclusionOur study found no significant associations of dietary intakes of isoflavones, soy protein, and soy foods with the risks of all-cause, cancer, and CVD mortality.